Secondary dispersion halos as a prospecting Indicator of platinum metal mineralization on the example of the Kamenushinsky massif (Middle Urals) - Minibaev Aleksandr M. (Федеральное государственное бюджетное образовательное учреждение высшего образования «Санкт-Петербургский горный университет», 2018)
The paper discusses the results of bulk rock geochemical sampling of the Kamenushinsky massif eluvial-deluvial deposits and the massifs bedrocks spectral analysis data. Evaluation of secondary dispersion halos using twodimensional modeling and multivariate statistic processing of the results have allowed establishing the spatial collocation of platinum and chromium anomalies and high correlation between these elements. These facts confirm the considerable contribution of chromite-platinum mineralization to the primary ores of the entire Kamenushinsky massif. The geological observations and rocks chemical composition analysis has revealed that uranium and barium anomalies are associated with the areas of gabbro and granitoids dike bodies. The insignificant overlapping of uranium and barium anomalies with platinum and chromium ones, as well as the negative correlation between these two groups of elements, is inconsistent with earlier conclusions on the spatial association of platinum mineralization with gabbro and granitoids dikes and a possible connection between these dikes and platinum metal mineralization zones.
Keywords: Kamenushinsky massif; bulk rock geochemical sampling; secondary dispersion halos; platinum; chromite; mineralization; dikes